ISOLASI DAN IDENTIFIKASI MORFOLOGIS NEMATODA ENTOMOPATOGEN DARI LAHAN PERTANAMAN SEMUSIM KEBUN PERCOBAAN FAKULTAS PERTANIAN DENGAN MENGGUNAKAN UMPAN LARVA Tenebrio molitor L. (Coleoptera : Tenebrionidae) - Saputra, Obhy Gartio; Salbiah, Desita; Sutikno, Agus (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The use of synthetic pesticide give many negative impacts, therefore need to do the right control with microorganism utilize. That potentially microorganism such as entomopathogenic nematode. The research aims to isolate and obtain the entomopathogenic nematode isolat from the annual crops field at Agriculture Experimen Station in Faculty of Agriculture Riau University by using bait larvae of Tenebrio molitor. The research was carried out with survey methode. The sample were isolated from mustard greens field, papaya field and corn field at Agriculture Experimen Station. Data obtained were descriptive statistically analyzed and displayed in the form of picture. The results showed that isolation by using larvae of T. molitor had entomopathogenic nematode with the characteristics larvae of T. molitor which infected by entomopathogenic nematode were discharge of movement activity, motionless and finally the larvae was die with the change of skin colour from light brown to caramel. Another symptom was seen is larvae body became flabby, although that body shape still whole. The larvae colour change from light brown to caramel showed that larvae was infected by Steinernematidae family of entomopathogenic nematode. Steinernematidae family of entomopathogenic nematode had general and particural morphological characteristic. They had smooth head and not realated, pointed short tail, the vulva are jutting out and is located in the middle, nerves ring in anterior. The particular characteristic of Steinernematidae was they had no bursa at tail part.Â Keywords : isolation, identification, entomopathogenic nematode, Tenebrio molitor